1990
DOI: 10.1172/jci114736
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electrogenic Na+ transport across rat inner medullary collecting duct by glucocorticoid and by mineralocorticoid hormones.

Abstract: We have investigated the effect of steroid hormones on Na' transport by rat renal inner medullary collecting duct (IMCD) cells. These cells, grown on permeable supports in primary culture, grow to confluence and develop a transmonolayer voltage oriented such that the apical surface is negative with respect to the basal surface. The results of these experiments demonstrate that this voltage is predominantly (or exclusively) the result of electrogenic Na' absorption. Na' transport can be stimulated two-to fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 56 publications
2
48
0
1
Order By: Relevance
“…Using pharmacological inhibitors, we previously showed that MR and GR both contributed to the induction of early aldosterone targets (4). This was consistent with the known contribution of each receptor to aldosterone action (20). To demonstrate hormone receptor-mediated regulation of the Per1 gene, we used an RNA silencing (siRNA) approach to knock down expression of MR, GR, or both receptors.…”
Section: Figuresupporting
confidence: 66%
“…Using pharmacological inhibitors, we previously showed that MR and GR both contributed to the induction of early aldosterone targets (4). This was consistent with the known contribution of each receptor to aldosterone action (20). To demonstrate hormone receptor-mediated regulation of the Per1 gene, we used an RNA silencing (siRNA) approach to knock down expression of MR, GR, or both receptors.…”
Section: Figuresupporting
confidence: 66%
“…As the final structure capable of altering the composition of the urine, the renal inner medullary collecting duct (IMCD)1 plays 1. Abbreviations used in this paper: IMCD, inner medullary collecting duct; CCD, cortical collecting duct; ISc, short-circuit current; MC, mineralocorticoid; GC, glucocorticoid; GAPDH, glyceraldehydephosphate dehydrogenase.…”
Section: Introductionmentioning
confidence: 99%
“…The secretion and absorption of NaCl in IMCD are orchestrated by the actions of various hormones, like aldosterone andor antidiuretic hormone. The mineralocorticoids stimulate electrogenic Na' transport [32] and generate a lumen-negative transepithelial voltage that provides an electrochemical driving force for C1-diffusion across the tight junction [7]. However, antidiuretic hormone (for example during dehydration) increases intracellular CAMP levels 1331 and provides an apical CAMP-stimulated electrogenic C1-secretion [7].…”
mentioning
confidence: 99%